2021
DOI: 10.1021/acs.jpca.1c01836
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrollable Modulation of Frontier Molecular Orbital Energy Levels of Cyclopentenone-Based Diarylethenes

Abstract: Photoswitchable diarylethenes provide a unique opportunity to optically modulate frontier molecular orbital energy levels, thereby opening an avenue for the design of electronic devices such as photocontrollable organic field-effect transistors (OFETs). In the present work, the absolute position of the frontier orbital levels of nonsymmetrical diarylethenes based on a cyclopentenone bridge has been studied using cyclic voltammetry and density functional theory (DFT) calculations. It has been shown that varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The Z chalcone isomer stability calculated with the (GO + DC) procedure is (3,5) > anti (2,4) > anti (2,5) > syn (3,4) > (2,6) > anti (2,3), which is similar to that obtained from (GO/ SPDC), as shown in Table 1. The chromen isomer stability order is (5,8a) > (5,8) > (6,8) > (5,7) > (5,6) > (6,7), which agrees completely with that obtained using (GO/SPDC).…”
Section: Stability Of Isomerssupporting
confidence: 78%
See 2 more Smart Citations
“…The Z chalcone isomer stability calculated with the (GO + DC) procedure is (3,5) > anti (2,4) > anti (2,5) > syn (3,4) > (2,6) > anti (2,3), which is similar to that obtained from (GO/ SPDC), as shown in Table 1. The chromen isomer stability order is (5,8a) > (5,8) > (6,8) > (5,7) > (5,6) > (6,7), which agrees completely with that obtained using (GO/SPDC).…”
Section: Stability Of Isomerssupporting
confidence: 78%
“…In Part I, we investigated the stability of each conformer, and the results indicated that the syn (2,3), syn (2,4), and syn (2,5) conformers are more stable than their anti-counterparts. However, the anti (3,4) of the E chalcone was more stable than the syn (3,4) E chalcone. Nevertheless, the Z chalcone series with the anticonformers are more stable than the syn conformers for (2,3), (2,4), and (2,5), while the syn (3,4) Z chalcone is more stable than its anti-counterpart.…”
Section: Stability Of Isomersmentioning
confidence: 88%
See 1 more Smart Citation
“…Several authors have studied numerous DTE derivatives from both experimental 1–4,11–18 and theoretical 1,2,5,16–25 perspectives for more than three decades. Although many aspects of DTEs have been clarified, the control of the QY of the photocyclization and photoreversion is still a puzzle.…”
Section: Introductionmentioning
confidence: 99%
“…2 These features make them excellent candidates for developing modern technologies, for example, application of molecular photoswitches 1,2 and photomolecular motors 2,7 in nanomachines 8 and molecular electronic devices. 7,[9][10][11] Several authors have studied numerous DTE derivatives from both experimental [1][2][3][4][11][12][13][14][15][16][17][18] and theoretical 1,2,5,[16][17][18][19][20][21][22][23][24][25] perspectives for more than three decades. Although many aspects of DTEs have been clarified, the control of the QY of the photocyclization and photoreversion is still a puzzle.…”
Section: Introductionmentioning
confidence: 99%